Wear behaviour of Ni-Cr-Mo-V steel under dry sliding - Pathak J.P.; Mohan S. (My University, 2025)
Dry-sliding wear behaviour of bainitic structure (BS) and tempered martensitic structure (TMS) of Ni-Cr-Mo-V steels have been investigated at room temperature, using a pin-on-disc wear testing rig. These two microstructures reveal the rising trend of wear rate with normal applied load and sliding velocities in the initial stages; but once a maxima is attained in wear rate, then wear rate decreases with further increase in applied load or sliding velocity. It is also observed that wear resistance of TMS steel is superior to BS steel, but the difference in wear rate is not significant. The stereo-micrographs of debris generated show the oxidative and metallic modes of wear for both the microstructures. The study of worn surface clearly highlights the oxide formation, smearing of surface and distortion associated with straining and plastic deformation. The micro-ploughing, spalling and subsequent detachment of oxides and metallic surface layers from the worn-out surface of the pin specimen are the dominant mechanisms of the wear under different conditions of applied loads and sliding velocities. The wear rate is very much influenced by the yield strength and hardness of the bainitic and tempered martensitic steels.